2017
DOI: 10.3389/fimmu.2017.00775
|View full text |Cite
|
Sign up to set email alerts
|

TLR7/TLR9- and B Cell Receptor-Signaling Crosstalk: Promotion of Potentially Dangerous B Cells

Abstract: B cells are capable of receptor-mediated responses to foreign antigens. Recognition of microbial-derived nucleic acid (NA) by toll-like receptors (TLRs) 7 and 9 in B cells has been substantiated. Endogenous NA released from damaged or dying cells can also be immunogenic in certain contexts and can incite aberrant activation of B cells. When TLR-driven B cell receptor (BCR)-activated B cells are not properly constrained, pathologic autoantibodies are produced. It is also clear that endosomal TLR7/TLR9 can opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 78 publications
2
89
0
Order By: Relevance
“…It was recently shown that TLR4 activation plays a key role in promoting the maturation of immature and transitional B cells . Recognition of nucleic acids (NAs) by TLRs 7 and 9 on B cells results in aberrant B‐cell activation, with subsequent production of proinflammatory cytokines . Potential NAs stimulating B cells in murine BA may include microbially derived NAs (i.e., RRV) or endogenous NAs from damaged bile duct epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that TLR4 activation plays a key role in promoting the maturation of immature and transitional B cells . Recognition of nucleic acids (NAs) by TLRs 7 and 9 on B cells results in aberrant B‐cell activation, with subsequent production of proinflammatory cytokines . Potential NAs stimulating B cells in murine BA may include microbially derived NAs (i.e., RRV) or endogenous NAs from damaged bile duct epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…(44) Recognition of nucleic acids (NAs) by TLRs 7 and 9 on B cells results in aberrant B-cell activation, with subsequent production of proinflammatory cytokines. (21,45) Potential NAs stimulating B cells in murine BA may include microbially derived NAs (i.e., RRV) or endogenous NAs from damaged bile duct epithelial cells. There is a paucity of data on the role of the B cell in innate immune activation, and this area warrants further investigation in BA.…”
Section: Discussionmentioning
confidence: 99%
“…Most complex antigens will engage other receptors on the B cell in addition to the BCR. The ligation of some co-receptors, such as toll-like receptors (TLRs) or complement receptors (CR2), leads to amplification and possibly qualitative modification in the BCR signal (Carroll and Isenman, 2012;Suthers and Sarantopoulos, 2017). Co-receptor engagement may also reduce the threshold of antigen needed to activate B cells.…”
Section: Early B Cell Activationmentioning
confidence: 99%
“…9 Understanding the sequence of events that leads to the breakdown of follicular exclusion barrier provides insights into the chain of events that can lead to follicular translocation of B cells and autoantigens in SLE. [156][157][158][159][160] Secondary events of this process are twofold. 2,140,143,152 Related to this is the well-established interaction of such apoptotic cell debris with disposal mechanisms including uptake by DCs including plasmacytoid dendritic cells (pDCs), and with B-cells through their BCR antigen receptor.…”
Section: Breakdown Of the Mzm Follicular Exclusion Barrier In Slementioning
confidence: 99%
“…20,61,78,80,81,[155][156][157] In SLE, such clearance mechanisms can lead to the localization of apoptotic cell debris in the endosome and induction of type l interferons via stimulation through the endosomal TLRs including TLR7 and TLR9. [156][157][158][159][160] Secondary events of this process are twofold. First, there is increased production of type l interferon, which is well-established as being associated with SLE.…”
Section: Breakdown Of the Follicular Exclusion Barrier To Autoantigmentioning
confidence: 99%